PENGARUH MODEL DISCOVERY LEARNING BERBANTUAN MEDIA AUDIOVISUAL TERHADAP KETERAMPILAN MENULIS TEKS ANEKDOT SISWA KELAS X SMA NEGERI 1 LEMBAH GUMANTI KABUPATEN SOLOK - Tressyalina, Mayora, Syahrul R., (Universitas Negeri Padang, 2017)
In this study, theoretical concept of discovery learning are reviewed the influence of discovery learning style use media audiovisual to assist students writing skill Anecdote text at X grade of SMA Negeri 1 Lembah Gumanti. The data collections of this study are results of use Anecdote writing skill text between an experiment and control class. The process of collecting data are use extend of learning anecdote skill text by discovery learning style with media audiovisual assistant both an experiment class. Test by anecdote writing skill text work show on students. The writing Anecdote skill text between an experiment and control class was researcher used to show there comparisons among the influence of discovery learning style with assist audiovisual media accompanying hypothesis experiment abbreviation. The results of this study showed that (1) using Anecdote writing skill text at students X Grade of SMA Negeri 1 Lembah Gumanti without use discovery learning style with assist media audiovisual have qualification kind. (2) That anecdote writing skill text at students X Grade of SMA Negeri 1 Lembah Gumanti without use discovery learning style with assist media audiovisual also have qualification kind. (3) Based on abbreviation hypothesis experiment there are significant conclusions of influence toward discovery learning style with assist media audiovisual on anecdote skill writing text on students learning process of SMA Negeri 1 Lembah Gumanti. Kata kunci: Pengaruh, model discovery learning berbantuan media audiovisual, menulis teks anekdot